Predicting mathematics teaching anxiety from mathematics performance and mathematics anxiety - Abuan, Johmar E.; Taganap, Eduard C. (Intelektual Pustaka Media Utama, 2025)
This study aims to identify the predictors of mathematics teaching anxiety among Filipino preservice elementary teachers. This research utilized a descriptive-correlational research design. Data were obtained through a descriptive survey from 145 students, selected using stratified random sampling from a state university in Central Luzon, Philippines. The study administered the adopted mathematics anxiety scale-UK, the mathematics teaching anxiety scale, and a mathematics test. According to our findings, mathematics performance and mathematics teaching anxiety were negatively correlated. On the other hand, a positive correlation emerged between mathematics anxiety and mathematics teaching anxiety. Furthermore, this study employed stepwise regression analysis. Our results showed that “mathematics evaluation anxiety”, a parameter of mathematics anxiety significantly predicts respondents’ mathematics teaching anxiety. Examining the predictors of mathematics teaching anxiety is crucial for improving teacher preparation, enhancing teaching quality, and creating a positive learning environment.